Crosstalk between the tumor immune microenvironment and metabolic reprogramming in pancreatic cancer: new frontiers in immunotherapy - Shi, Taijin; Cui, Xiaoyan; Wang, Junlin; Liu, Guangqia; Meng, Jiayin; Zhang, Yingjie (Frontiers in Immunology, 2025)
In recent years, the incidence and mortality of pancreatic cancer (PC) are increasing year by year. The highly heterogeneous nature of PC, its strong immune escape ability and easy metastasis make it the most lethal malignant tumor in the world. With the rapid development of sequencing technology, the complex components in the tumor microenvironment (TME) of PC have been gradually revealed. Interactions between pancreatic stellate cells, tumor-associated fibroblasts, various types of immune cells, and cancer cells collectively promote metabolic reprogramming of all types of cells. This metabolic reprogramming further enhances the immune escape mechanism of tumor cells and ultimately induces tumor cells to become severely resistant to chemotherapy and immunotherapy. On the one hand, PC cells achieve re and rational utilization of glucose, amino acids and lipids through metabolic reprogramming, which in turn accomplishes biosynthesis and energy metabolism requirements. Under such conditions, tumorigenesis, proliferation and metastasis are ultimately promoted. On the other hand, various types of immune cells in the tumor immune microenvironment (TIME) also undergo metabolic reprogramming, which leads to tumor progression and suppression of anti-immune responses by inhibiting the function of normal anti-tumor immune cells and enhancing the function of immunosuppressive cells. The aim of this review is to explore the interaction between the immune microenvironment and metabolic reprogramming in PC. The focus is to summarize the specific mechanisms of action of metabolic reprogramming of PC cells and metabolic reprogramming of immune cells. In addition, this review will summarize the mechanisms of immunotherapy resistance in PC cells. In the future, targeting specific mechanisms of metabolic reprogramming will provide a solid theoretical basis for the development of combination therapies for PC.